Creation of an NCI comparative brain tumor consortium: informing the translation of new knowledge from canine to human brain tumor patients. Issue 9 (1st September 2016) - LeBlanc, Amy K.; Mazcko, Christina; Brown, Diane E.; Koehler, Jennifer W.; Miller, Andrew D.; Miller, C. Ryan; Bentley, R. Timothy; Packer, Rebecca A.; Breen, Matthew; Boudreau, C. Elizabeth; Levine, Jonathan M.; Simpson, R. Mark; et al.
Abstract: On September 14–15, 2015, a meeting of clinicians and investigators in the fields of veterinary and human neuro-oncology, clinical trials, neuropathology, and drug development was convened at the National Institutes of Health campus in Bethesda, Maryland. This meeting served as the inaugural event launching a new consortium focused on improving the knowledge, development of, and access to naturally occurring canine brain cancer, specifically glioma, as a model for human disease. Within the meeting, a SWOT (strengths, weaknesses, opportunities, and threats) assessment was undertaken to critically evaluate the role that naturally occurring canine brain tumors could have in advancing this aspect of comparative oncology aimed at improving outcomes for dogs and human beings. A summary of this meeting and subsequent discussion are provided to inform the scientific and clinical community of the potential for this initiative. Canine and human comparisons represent an unprecedented opportunity to complement conventional brain tumor research paradigms, addressing a devastating disease for which innovative diagnostic and treatment strategies are clearly needed.